Low Voltage Ride-through for Doubly Fed Induction Generator Using Battery-Storage System - D.V.N. Ananth; G.V. Nagesh Kumar (Institute of Advanced Engineering and Science, 2016)
In this paper, enhanced field oriented control technique (EFOC) was adopted in Rotor Side Control (RSC) of DFIG converter for improved response during severe faults. The work is intended to damp pulsations in electromagnetic torque, improve voltage mitigation and limit surge currents and to enhance the operation of DFIG during voltage sags. The converter topology uses a battery energy storage system with capacitor storage system to further enhance operation of DFIG during faults. The battery and capacitor system in coordination provide additional real and reactive power support during faults and nearly constant voltage profile at stator and rotor terminals and limit overcurrents. For EFOC technique, rotor flux reference changes its value from synchronous speed to zero during fault for injecting current at the rotor slip frequency. In this process DC-Offset component of flux is controlled, decomposition during overvoltage faults. The offset decomposition of flux will be oscillatory in a conventional FOC, whereas in EFOC it will damp quickly. A comparison is made with proposed methodology with battery energy storage system and a conventional system. Later the system performance with under voltage of 50% the rated voltage with fault at PCC during 0.8 to 1.2 seconds is analysed using simulation studies.